1971
DOI: 10.1139/b71-185
|View full text |Cite
|
Sign up to set email alerts
|

An open gas-exchange system for the simultaneous measurement of the CO2 and 14CO2 fluxes from leaves

Abstract: An open gas exchange system that uses an infrared gas analyzer and an ionization chamber to measure CO2 and 14CO2 is described. The system will continuously measure the CO2 and 14CO2 exchange from a leaf within 30 s after the 14CO2 gas mixture is supplied to the leaf. Measurements are obtained under steady rate conditions since the 14CO2 gas mixture is supplied at a constant composition from pressurized cylinders. Methods of determining true photosynthesis, apparent photosynthesis, CO2 evolution, and the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…the precursor for sorbitol (10,18,20), is an activator of sucrose-phosphate synthetase (24), a key enzyme of the sucrose pathway. (14). Moreover, a preliminary experiment (I showed that the leaf blade thickness of fixe4 mature leaves was between 0.14 and 0.18 we can assume that the Geiger-Muller tub( activity in the whole thickness of the leaf redistribution of radioactivity among indivi had created little artifact.…”
Section: Partitioning Of Photosynthetic Carbonmentioning
confidence: 94%
“…the precursor for sorbitol (10,18,20), is an activator of sucrose-phosphate synthetase (24), a key enzyme of the sucrose pathway. (14). Moreover, a preliminary experiment (I showed that the leaf blade thickness of fixe4 mature leaves was between 0.14 and 0.18 we can assume that the Geiger-Muller tub( activity in the whole thickness of the leaf redistribution of radioactivity among indivi had created little artifact.…”
Section: Partitioning Of Photosynthetic Carbonmentioning
confidence: 94%
“…Photosynthesis was calculated based on the 14 CO2 fixed during 30 s exposures and our estimates thus represent values closer to gross, rather than net, photosynthesis. 6 Details of these methods and the calculations were described previously. 5 Needle water potential (measured by pressure chamber) averaged -11.4 bars during the season and ranged between -14 and -8 bars.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A cylinder (4-0 dm 3 ) containing compressed dry air and 14 CO 2 was prepared as described by Ludwig and Canvin (1970). Ten cm 3 air with a known amount of I4 CO 2 was taken from the cylinder using a syringe and, after the system was closed, injected into the cuvette where it was rapidly distributed by the fan.…”
Section: Gas Exchange Analysis With Intact Leavesmentioning
confidence: 99%